The Influence of Parental Attention on the Academic Achievement of Elementary School Students - Siti Kholidatur Rodiyah; Salwa Sabrina; Maulidia Ilham Fadilah (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
This study aims to analyze the influence of parental attention on student learning achievement at the Elementary School level. Through a qualitative literature study, this study examines various relevant previous research results in order to obtain a comprehensive understanding of the contribution of parental attention to student academic achievement. The results of the analysis indicate that parental attention, which is manifested through mentoring, supervision, motivation, and provision of learning facilities, has a significant influence in improving student learning achievement. This study emphasizes the importance of active parental involvement in the child's education process as a major factor in optimizing learning achievement in elementary schools.  Research results show that students who receive more attention and support from their parents tend to have better academic achievements compared to students who receive less attention. Forms of attention can include helping the child study at home, providing motivation, and showing interest in the child's school activities. These findings emphasize that active parental involvement plays a significant role in supporting children's academic success at the elementary school level.